Victorian Specialist Immunisation Services (VicSIS) - bolstering adult clinics for COVID-19 vaccines - Sally F. Gordon; Elise Virah Sawmy; Eleanor Duckworth; Michelle Wolthuizen; Hazel J. Clothier; Malinda Chea; Naveen Tenneti; Ngaree Blow; Jim P. Buttery; Joseph de Luca; Tony M. Korman; Sara Barnes; et al. (Taylor & Francis Group, 2022)
The Victorian Specialist Immunization Services (VicSIS) was established in Victoria, Australia, in February 2021, aiming to enhance vaccine safety services for Coronavirus disease (COVID-19) vaccines. VicSIS supports practitioners and patients with complex vaccine safety questions, including those who experience adverse events following immunization (AEFI) after COVID-19 vaccines. VicSIS provides individual vaccination recommendations, allergy testing, vaccine challenges, and vaccination under supervision. VicSIS initially comprised of eight adult COVID-19 specialist vaccination clinics, subsequently, expanding to better support pediatric patients as the Australian vaccine roll-out extended to adolescents and children. Since their establishment to September 2021, the inaugural VicSIS clinics received a total of 26,401 referrals and reviewed 6,079 patients. Consults were initially predominantly for pre-vaccination reviews, later predominantly becoming post-vaccination AEFI reviews as the program progressed. Regardless of the type of consult, the most common consult outcome was a recommendation for routine vaccination (73% and 55% of consult outcomes respectively). VicSIS is an integral component of the COVID-19 vaccination program and supports confidence in COVID-19 vaccine safety by providing consistent advice across the state. VicSIS aims to strengthen the health system through the pandemic, bolstering specialist immunization services beyond COVID-19 vaccines, including training the next generation of vaccinology experts.